Anthropogenic disturbance and habitat loss for the red-listed Asiatic black bear (Ursus thibetanus): Using ecological niche modeling and nighttime light satellite imagery. (November 2015) - Escobar, Luis E.; Awan, Muhammad Naeem; Qiao, Huijie
Abstract: Habitat loss is a critical factor driving extinction of biodiversity worldwide, with models of future land use anticipating increases in rates of destruction of native habitats worldwide. The Asian black bear ( Ursus thibetanus ) is a red-listed species with a broad geographic range that has been fragmented dramatically by land use change. Remaining populations of U. thibetanus occupy diverse habitats, ranging from highlands to coastal regions. We integrated ecological niche models (ENMs) with nighttime satellite imagery to identify areas suitable for U. thibetanus after anthropogenic alteration. We found that at least 10% of the potential distributional area for the species is not suitable owing to urban or suburban encroachment. U. thibetanus seems to persist in highland areas, characterized by low temperature and high precipitation, whereas humans concentrate in lowlands and less-extreme climatic conditions. ENMs based solely on climate frequently overestimate suitable areas available for species; nighttime light imagery offers a robust alternative to refining estimates of species' ranges, designing protected areas and corridors, prioritizing threatened species, and determining areas of human–wildlife conflict across broad areas. Our approach is transferable to other taxa and contexts, and should be considered in conservation planning and policy implementation. Graphical abstract: Highlights: We mapped changes in the range of Ursus thibetanus using ecological niche modeling. Nighttime light provided information on habitat loss and improved model estimations. Suitable areas for Ursus thibetanus are predicted to decline by at least in 10%. We present a useful and novel method to assess suitable areas for threatened species.